Assessment of Emotional and Behaviour Disorders of Girls Living in Restricted Environment and Intervention Strategies Through Physical Activity (Baltic Journal of Sport and Health Sciences, 2018)
Background. Students with emotional and behavioural disorders (EBD) represent one of the most challenging groups not only to provide effective educational services, but often present complex challenges for schools, families, and society. There is a lack of information about concrete research-based interventions and practices which could be helpful for delinquent students with EBD to cope with problem behaviour more effectively. The aim of the study was to assess the emotional and behaviour disorders of girls living in socialization centres and to review intervention strategies for changing behaviour through physical activity. Methods. The study was conducted in two Children Socialization Centres where 50 girls aged 12 – 18 are housed following the decision of Child Welfare Commission. Behaviour Assessment System for Children (BASC-2), a Self-Report Personality Scale was used to find out emotional and behavioural disorders of girls. Results. Analysis of our study results reveals that the girls with delinquent behaviour living in CSC show the risk of having problems in school, high level of social stress, anxiety, sense of inadequacy, atypicality, attention problems, hyperactivity and lower levels of self-esteem, self-reliance, interpersonal relations. The results support the conclusions of other studies which found significant relations between EBD students and weak levels of social skills, self-esteem and self-efficacy, cooperation.Conclusion.  Sport  and  physical  activity  settings  are  effective  intervention  setting  for  creation,  practicing and maintenance of pro-social behaviour and emotion managing; furthermore those skills could be transferred to community settings in everyday life. The best education setting for EBD students could be provided in inclusive environment, where the positive behaviour skills could be copied and maintained.Keywords: emotional and behavioural disorders, intervention strategies, delinquent behaviour, restricted environment.